Time to kill the soldier's experience of war in the West, 1939-1945 - Addison, Paul; Calder, Angus (Pimlico, 1997)
This is an exploration of the realities of soldiering across the ranks in World War II. A distinguished cast of historians have contributed, and look at the conditions in which the soldiers of many different countries lived and died, as well as at their hopes and fears and experience of battle.